Analysis of Foreign Experience in Designing Architectural and Spatial Solutions of Medium-Rise Residential Buildings (Eurasian Research Bulletin, 2023)
The article is devoted to the analysis of modern foreign experience of design and construction in the field of architecture. Analyzing the attempts of foreign experts in architecture to improve medium-rise residential buildings in order to make it more comfortable and accessible to the general mass of consumers.